Bilateral distal ureteral transection in the setting of blunt trauma. Issue 1 (20th June 2018) - Raygor, Desiree; Cunningham, James; Costa, Joseph; Crandall, Marie; Skarupa, David
Abstract : A 69-year-old obese man was involved in a high-speed head-on motor vehicle collision. He was tachycardic and normotensive on arrival. He subsequently developed hemodynamic instability requiring blood transfusion. On examination he had bilateral pneumothoraces, an anterior-posterior compression (APC) pelvic fracture, an open wound at the left groin, and gross hematuria after Foley catheter placement. CT imaging revealed hemoperitoneum, right hepatic lobe grade II lacerations, splenic laceration, mesenteric root injury with extravasated contrast, intraperitoneal and extraperitoneal bladder rupture, bilateral ureteral injuries at the level of the pelvic inlet (see figure 1 ), APC pelvic fracture, bilateral rib fractures, pneumothoraces, and pulmonary contusions. He underwent emergent exploratory laparotomy. Exploration confirmed the injuries noted on the CT scan. Hepatorrhaphy with abdominal and preperitoneal pelvic packing was performed. A large anterior bladder wall injury was visualized. Neither ureteral orifice was seen. The right ureter was completely transected at the level of the pelvic brim. The left ureter was decompressed and the full extent of its injury was not determined; however, the bladder injury left concern for a distal avulsion. The patient continued to be in shock. What would you do?: Reconstruct the urinary bladder and reimplant bilateral ureters. Ligate the ureter and prepare for pelvic embolization and nephrostomy tubes. Continue to explore looking for the full extent of the left ureter. Externalize the ureters to the abdominal wall with the open abdomen.